The Effect of Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior on Effectiveness of Electrical Parts Industries in Thailand - Sananuamengthaisong, Manisara (Journal for Strategy and Enterprise Competitiveness, 2022)
This study investigates job satisfaction, organizational commitment and organizational citizenship behavior effect on organization effectiveness of electrical parts industries in Thailand are the population of the study. Furthermore, this research, a source of database is used as electrical parts industries in Thailand. The returned and valid questionnaire results were 333 samples and key participant is human resource managers or general managers in each of company. The results show that job satisfaction and organizational commitment influence on organizational citizenship behavior. The three dimensions of organizational citizenship behavior: altruism, compliance, loyalty some significant an effect on organizational effectiveness. Also, job satisfaction, organizational commitment and organizational citizenship behavior has a potential positive influence on organizational effectiveness. Potential discussion with the research results is effectively implemented in the study. Theoretical and managerial contributions are explicitly provided. Conclusion and suggestions are also providing for further research.